Penerapan Metode Case Based Reasoning Dalam Deteksi Dini Penyakit Kejang Demam (Febrile Convulsions) Di Rumah Sakit Rafflesia Bengkulu - Khairil Fajri NST; Khairil Khairil; Eko Suryana (Jurnal Media Infotama, 2024)
Rafflesia Bengkulu Hospital is one of the health facilities in Bengkulu City. At the Bengkulu Rafflesia Hospital, every month there are patients diagnosed with febrile convulsion (febrile convulsions), some experiencing inpatient and outpatient treatment. The application of the Case Based Reasoning Method in early detection of febrile convulsions at Rafflesia Hospital Bengkulu can be used as a forum to help patients find out the initial or early diagnosis of febrile convulsions based on the symptoms felt by the patient through web-based expert system which can be accessed online via the URL link https://sistempakarkejangdemam.my.id/ with an internet connection. Based on 3 (three) cases tested on the expert system for early detection of febrile convulsions at Rafflesia Hospital Bengkulu, it was concluded that the expert system application was able to detect early febrile convulsions according to the symptoms that had been selected. Based on the system testing that has been carried out, it can be concluded that the functional application of the Case Based Reasoning Method in early detection of febrile convulsions at Rafflesia Hospital Bengkulu has been running well and can provide consultation results based on symptoms that have been answered by the community through stages of the Case Based Reasoning (CBR) method.